Identification of quality characteristics for mobile applications - Maia, Vitor Carneiro (2019)
[EN] Mobile applications hold a well-established market, and they became popular since the creation of the app stores’ distribution model. These systems are directly impacted by context variations, by the usage of mobile device’s sensors, by usability and many other particular features that makes mobile applications different from other types of software. App stores provide quality guidelines with generic recommendations for publishing apps, but these recommendations do not cover all mobile application needs and usages. Quality models for quality assessment of software product are generalpurpose and made to be applied to any kind of software product. However, these models may be particularized for specific contexts. This paper proposed a set of context-specific quality characteristics for mobile applications, based on the particularization of quality models defined in international standards. This set was used to extend the ISO/IEC 25010 quality models. The identification was performed by conducting a systematic mapping and a survey with mobile application users. One the quality characteristics are identified, an evaluation procedure for mobile application is also proposed. The procedure is adapted from an existing software evaluation model. The feasibility of using this procedure was verified through the evaluation of a mobile banking application, already on the market.